(untitled) (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2015)
The contestation of paradigms within the discipline of applied linguisticsmay broadly be categorised as a conflict of modernist versus postmodernistapproaches. While postmodernism has been in the ascendancy in applied linguistics since the last decade of the previous century, it is both divided and currently being challenged by paradigms that hark backto modernism. This paper will discuss a variant of one still influentialapplied linguistic paradigm, ethnography, as a potential growth point for postmodernist views, and one that may well serve to resist the modernist challenge presented by dynamic systems theory. In acknowledging subjectivity and human agency, this variant, autoethnography, recognises that science is not neutral, and shows how scholars working within the mainstream may be able to present their beliefs and commitments in a way that opens these up for consideration and discussion. In doing that, autoethnography may have wider application than in its initial target domains, the social sciences and the humanities. The contestation that it presents within applied linguistics, however, is as unlikely to beconclusive as in any other paradigm conflict. For the present, the greatercontribution of autoethnography lies in making it possible to articulate and open for discussion the ways in which belief and commitment are presented in scholarly work.